He Analysis of Global Diversity in The Elt Textbook for Junior High School Students - Syifa Ainun Najwa (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
In learning activities, character education is a system of inculcating character values in students, which include components of knowledge, awareness, willingness, and action to carry out these values, both towards God Almighty, oneself, respect, courtesy, and others, which in the end educational process is to make Indonesian people altogether (Dewi and Alam, 2020). It is suggested in the emancipated curriculum that English teachers should include a dimension of global diversity in their ELT materials. It is essential to instill values in students such as caring, honesty, fairness, responsibility, and respect for themselves and others. The primary purpose of education for tolerance is to help students develop strategies that contribute to creating a world order that fosters social justice (Tican, 2020). Therefore, it must be implemented early because the implementation process is not instant and takes quite a long time to build good student habits. These methods can support students' intellectual, social, emotional, and ethical growth and are dedicated to helping them develop their sense of responsibility and become compassionate and active citizens (Sight, 2019). Therefore, the government is building a bridge through textbooks by including character education.
Reupload File Repositori 2 Februari 2026_Taufik/Lia
Keywords: Analysis Of Global; Elt Textbook